Factors impacting diverging paths of renewable energy: A review. (January 2018) - Can Şener, Şerife Elif; Sharp, Julia L.; Anctil, Annick
Abstract: Considered an essential factor for countries' development, energy demand is growing worldwide. Unlike conventional sources, the use of renewable energy sources has multiple benefits, including increased energy security, sustainable economic growth, and pollution reduction, in particular greenhouse gas emissions. Nevertheless, there is a considerable difference in the share of renewable energy sources in national energy portfolios. This study conducts a systematic literature review to identify drivers and barriers which could help understanding the diverging paths of renewable energy deployment for countries. Among a total of 1431 academic studies, 60 qualitative and quantitative studies were identified using a multistage selection process. Designated manuscripts were explored in detail including publication years, length of the studies, countries represented, and renewable energy sources referenced. Factors explaining countries' renewable energy deployments were defined and organized into seven main categories: economic, environmental, political, regulatory, social, technical potential, and technological. Within these categories, economic considerations appeared most frequently across manuscripts, while environmental factors were least represented. These categories were then classified as drivers, barriers or undetermined towards renewable energy deployment based on a one-sample proportion statistical test. Economic, environmental, and social factors were found to be drivers, whereas political, regulatory, technical potential and technological factors were not classified as either a driver or a barrier (i.e., undetermined). Each main category contains several subcategories, among which only national income was found to have a positive impact, whereas all other subcategories were considered undetermined. No significant barriers to the deployment of renewable energy sources were found over the analyzed period.